Chiral and helical states in selective-area epitaxial heterostructure - Huimin Sun; Yu Huang; Mengyun He; Yu Fu; Sikang Zheng; Bin Zhang; Chen Wang; Qing Lin He (Communications Physics, 2023)
Abstract The quasi-1D chiral edge states in a quantum anomalous Hall insulator are dissipationless, while the 2D helical surface states in a topological insulator are insensitive to spin-independent scatterings due to the topological protection. Both serve as essential ingredients for topological electronics. Here, we integrate these states into a single device using selective area epitaxy based on the molecular beam epitaxy technique. The chiral edge state comes from the quantum anomalous Hall insulator Cr:(Bi,Sb)2Te3, while the helical surface state comes from the intrinsic topological insulator (Bi,Sb)2Te3 which only interfaces with a partial edge of the former, forming a selective-area heterostructure. At the heterointerface, the chiral state in Cr:(Bi,Sb)2Te3 is allowed to be scattered into (Bi,Sb)2Te3 so that the incoming current will be redistributed according to the coordination between the chirality and helicity. Our device enables the collaboration between chiral and helical states for low-dissipative transport with tunable current dimension.